Pengaruh Kualitas Pelayanan Akademik terhadap Kepuasan Mahasiswa Sekolah Tinggi Ilmu Ekonomi (STIE) Lamappapoleonro Soppeng - Surianti Surianti; Mattalatta Mattalatta; Hasmin Tamsah (Pascasarjana STIE Amkop Makassar, 2020)
This research was doing at STI E Lamappapoleonro Soppeng. Analysis data was using descriptive method and quantitative method. Namely by analyzed of linear regression to measure influence of academic service quality consist of tangibles, reliability, responsiveness, assurance, emphaty toward the satisfaction of students. Reseach result shown that tangible, reliability, responsiveness, assurance, and emphaty each other have positive influence, toward dependence variable (students satisfaction). By hypotesa analyze namely syncronisation analyze show that reliability and assurance are dominan factor which influence the satisfaction of students at STIE Lamappapoleonro Soppeng. Keywords: Satisfaction, tangibles, reliability, responsiveness, assurance, emphaty